"England Hath Long Been Mad": Declamatory Outcry and Prescient Dream in Richard III. (3rd April 2019) - Lansky, Melvin R.
Abstract : This paper continues the discussion of the role of the conscience in Richard III put forward in an earlier paper and explores the backdrop of ruthlessness in the play and the response in royal persons of adopting the role of conscience. The eerie ambience throughout the drama results in part from the taking of the role of conscience in the use of blessings, curses, prophecies, and dreams. I shall emphasize the importance of underlying shame dynamics. In the play blessings, curses, and prophecies take the form of declamatory proclamations made only by widowed women who were, had been in line to be, or had been, queens of England. The wish for magical revenge conveyed by their blessings, curses, and prophecies assumes a wishfully omnipotent stance on the part of the helpless widowed royal women, who deploy them. Additionally, after-worldly innuendos marking many speeches in the play add to its sinister ambience as it relates to the tottering world of England during the War of the Roses and its resolution by the accession of the House of Tudor. The ambience created by the wishfully omnipotent blessing and curses imparts a powerful sense of the uncanny not only on those receiving the blessing or curse, but on the audience experiencing the play. Dreams, which seem prescient only after the dream is dreamt, are reported by all the men of royal blood: King Edward IV, George, Duke of Clarence, Richard, Duke of Gloucester (later, King Richard III) and Lord Stanley, father-in-law of the Earl of Richmond, later King Henry VII. These blessings, curses, prophecies, and dreams cloak the play in an after-worldly and pervasive, omnipotent, and sinister ambience.